Vlog Youtube untuk Meningkatkan Keterampilan Berbicara Peserta Didik SMP Pada Materi Teks Tanggapan Kritis - Budiartati, Agung; Siswanto, Romi (Jurnal Nispatti, 2025)
Speaking skills as language skills that can be developed with the youtube vlog media. The purpose of the learning innovation work "Youtube Vlogs to Improve Junior High School Students' Speaking Skills on Critical Response Text Materials" is to describe that the YouTube vlog can be used as a learning medium to improve the speaking skills of Grade IX students on critical response text material. The research subjects were students of class IX. A qualitative descriptive approach was used in this study. The data collected in the form of numbers are then summarized descriptively. The results showed that YouTube vlogs can be used as a learning medium to improve the speaking skills of class IX students of SMP Negeri 2 Pasuruan on critical response text material. The use of YouTube vlogs shows the extraordinary skills of students, from the aspect of speaking skills and the ability to create YouTube vlogs. Of the 34 students, 96% stated that they were happy to create a YouTube vlog about coverage around the city where they live. Achievements above KKM 74.